1997
DOI: 10.1016/s0741-5214(97)70142-3
|View full text |Cite
|
Sign up to set email alerts
|

Arterial and venous repair with vascular clips: Comparison with suture closure

Abstract: Repair of 1 cm incisions in small-diameter arteries and veins with VCS clips results in wound healing as good as that achieved with standard suture closure, when assessed for patency, leakage, degree of narrowing, and intimal reaction. The time required for clip closure is considerably shorter than for suture closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 5 publications
1
37
0
Order By: Relevance
“…The speed with which the VCS clips can be applied is their main advantage over sutures. This advantage also has been pointed out in several vascular reconstruction procedures including arterial and venous anastomoses [2][3][4]. Use can be made of VCS clips in all vascular operations wherein time is of critical importance for a favorable outcome, as with organ transplantation [3] and management of multiple vascular injuries in trauma patients [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The speed with which the VCS clips can be applied is their main advantage over sutures. This advantage also has been pointed out in several vascular reconstruction procedures including arterial and venous anastomoses [2][3][4]. Use can be made of VCS clips in all vascular operations wherein time is of critical importance for a favorable outcome, as with organ transplantation [3] and management of multiple vascular injuries in trauma patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…The use of VCS clips in microvascular anastomoses has been well described previously [1]. Recently published experimental studies [2,4] suggest their applicability also in larger vessels. The purpose of this study was to evaluate the use of VCS clips for arteriotomy closure after embolectomy.…”
mentioning
confidence: 99%
“…However, reported benefits may offset the greater cost of these clips. In experimental studies, some authors have noted differences between nonpenetrating titanium clips and conventional sutures as regards the time taken to suture vascular walls, 1,2,7,12,19 and the mean vascular suturing time was significantly shorter when nonpenetrating titanium clips were applied, as compared with the time required to apply sutures. One study reported that nonpenetrating titanium clips saved up to 88% of the vascular suturing time compared with conventional sutures.…”
Section: Fig 8 Leakage Patterns Without Coverings Of Fibrin Glue Anmentioning
confidence: 99%
“…8 Clinical use of the VCS clip applier system  during the creation of an arteriovenous Brescia-Cimino fistula. Inlay shows four different sizes of the clip applier, everting forceps and a clip remover clips compared with sutures are a reduced anastomotic time 42,43 and a higher patency rate, probably related to an improved anastomotic healing pattern 5,6,43 -45 .…”
Section: Staples and Clipsmentioning
confidence: 99%